Computer Science & Technology Series : XXII Argentine Congress of Computer Science. Selected papers - Pesado, Patricia Mabel (2017)
CACIC’16 was the 22th Congress in the CACIC series. It was organized by the Computer Science Department at the School of Mathematics, Physics and Natural Sciences of the San Luis National University. The Congress included 13 Workshops with 136 accepted papers, 2 Conferences, 2 invited Tutorials, different meetings related with Computer Science Education (Professors, PhD students, Curricula) and an International School with 6 courses. CACIC 2016 was organized following the traditional Congress format, with 13 Workshops covering a diversity of dimensions of Computer Science Research. Each topic was supervised by a committee of 3-5 chairs of different Universities. The call for papers attracted a total of 185 submissions. An average of 2.5 review reports were collected for each paper, for a grand total of 462 review reports that involved about 176 different reviewers. A total of 136 full papers, involving 457 authors and 79 Universities, were accepted and 30 of them were selected for this book.